Impact of Teacher Certification on Teacher Motivation and Performance in State Senior High Schools in Ternate City, Indonesia - Albaar, Muhammad Ridha; Acim, Acim; Abdullah, Abubakar (Heca Sentra Analitika, 2023)
This study aims to analyze the impact of the teacher certification on teacher’s motivation and performance in State High Schools in Ternate City, Indonesia. This study uses a quantitative approach with a survey method. The sample used in this study was 193 teachers who were selected by proportionate random sampling. The data was analyzed using path analysis supported by descriptive statistical analysis. The results indicate that the teacher certification has a direct effect on teacher's motivation and performance. Therefore, improving the application of teacher certification, and achievement motivation can improve performance.